Design Tools Trash Automatic Using microcontroller Arduino - Alharis Ramadhani alharis; Karnadi (International Journal Cister, 2022)
Waste is a waste which can not be used again, which could in solid, liquid or gas form. If we hear that a litter box can make the surrounding environment uncomfortable because it causes a foul odor and can also be a source of diseases such as itching, diarrhea, flu, dengue, bacteria and others. This can provide problems where the author can take the initiative to conduct research to be able to design and build a garbage box tool that works automatically by using an ultrasonic sensor HC-SR04 as a detector of an object that is in front of him using a distance of 10 cm which can be adjusted according to the command so that that distance will be able to open the trash box if it exceeds the distance of 10 cm then the sensor will not work, to open the trash box using a micro servo given 10 seconds to open the trash box if it is more than the specified time then the trash box will work to close the trash box where the dfplayer and speakers work to issue sounds that will be determined according to commands such as saying thank you for throwing trash in its place for the control system using an Arduino microcontroller to run a program. the set to work properly. The purpose of building the garbage box tool is so that the community is protected from bacteria that exist on the surface of the garbage box that can cause disease and increase the community to always take care of the surrounding environment.